Verification of WRF model forecasts and their use for agriculture decision support in Bihar, India (MAUSAM, 2024)
Weather forecasting with high spatial resolution become increasingly relevant for decision support in agriculture and water management. Present work is carried out for verification of IMD-WRF Model rainfall forecast with 3 days lead time over Nalanda, Supaul and East Champaran districts in Bihar, India. The model’s skill up to a lead time of 3 days is evaluated with panchayat level daily in situ observations for Monsoon 2020 and 2021. Results show good agreement of forecast and observation throughout the domain and particularly over Supaul district, where about 70% of rain and no-rain days are correctly predicted for all panchayat. Also, FAR is .25 in almost all places.  This evaluation supports the use of WRF model forecast in agriculture up to 3 days in advance. However the quantitative verification suggests that model output is more reliable for moderate rainfall